Single-dose hydrocortisone administration does not enhance motor sequence learning or reward learning in humans - Günthner, Jan; Kiefer, Falk (Journal of psychopharmacology, 2018)
Despite its physiological and clinical relevance, the influence of hydrocortisone on specific kinds of learning remains relatively unexplored. We measured the effect of hydrocortisone on motor sequence and reward learning under non-stress conditions. For the study, 54 healthy young volunteers were randomly assigned to a dose of 20 mg hydrocortisone versus placebo. Participants performed two well-defined learning tasks. Hydrocortisone did not affect motor sequence or reward learning.
Gesehen am 16.05.2019